Specificity of thioredoxins and glutaredoxins as electron donors to two distinct classes of Arabidopsis plastidial methionine sulfoxide reductases B - Christina Vieira Dos Santos; Edith Laugier; Lionel Tarrago; Vincent Massot; Emmanuelle Issakidis‐Bourguet; Nicolas Rouhier; Pascal Rey (2007)
Methionine sulfoxide reductases (MSRs) A and B reduce methionine sulfoxide (MetSO) S ‐ and R ‐diastereomers, respectively, back to Met using electrons generally supplied by thioredoxin. The physiological reductants for MSRBs remain unknown in plants, which display a remarkable variety of thioredoxins (Trxs) and glutaredoxins (Grxs). Using recombinant proteins, we show that Arabidopsis plastidial MSRB1 and MSRB2, which differ regarding the number of presumed redox‐active cysteines, possess specific reductants. Most simple‐module Trxs, especially Trx m 1 and Trx y 2, are preferential and efficient electron donors towards MSRB2, while the double‐module CDSP32 Trx and Grxs can reduce only MSRB1. This study identifies novel types of reductants, related to Grxs and peculiar Trxs, for MSRB proteins displaying only one redox‐active cysteine.